Rechargeable fiber magnesium-oxygen battery based on negative electrode protection layer and preparation method of rechargeable fiber magnesium-oxygen battery

A zinc/magnesium-based protective layer on the magnesium negative electrode addresses the passivation issue, achieving high utilization and discharge efficiency in magnesium oxygen batteries.

CN119133729APending Publication Date: 2024-12-13FUDAN UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411205492.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The formation of a passivation layer on the magnesium negative electrode surface hinders the rechargeability of magnesium oxygen batteries, making it difficult to achieve efficient magnesium ion deposition and stripping.

Method used

A zinc/magnesium-based protective layer is applied to the magnesium negative electrode, which is constructed through a simple replacement reaction, providing magnesium ion conduction and electronic insulation, preventing passivation and ensuring reversible deposition and stripping reactions.

Benefits of technology

The protective layer enhances the magnesium negative electrode utilization rate to 99.8% and maintains a discharge voltage of 1.8V, enabling smooth charge and discharge cycles with reduced overpotential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133729A_ABST
    Figure CN119133729A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy batteries, and particularly relates to a rechargeable fiber magnesium oxygen battery based on a negative electrode protection layer and a preparation method thereof. The rechargeable fiber magnesium oxygen battery is of a coaxial structure, and comprises a metal magnesium wire negative electrode with a protective layer, an electrolyte layer and a platinum / carbon and ruthenium dioxide loaded carbon nanotube film air positive electrode from inside to outside in sequence. The preparation method comprises the following steps: preparing the metal magnesium wire surface protection layer, preparing the electrolyte, preparing the positive electrode and assembling the fiber magnesium oxygen battery. Wherein the zinc / magnesium-based surface protection layer is constructed through a replacement reaction, and can be firmly adhered to the surface of the magnesium negative electrode, so that the magnesium negative electrode is prevented from generating a passivation layer after being opposite to air. Meanwhile, the protective layer has the characteristics of magnesium ion conduction and electronic insulation, can promote transmembrane transmission of magnesium ions under the driving of an electric field, and ensures normal proceeding of a magnesium negative electrode deposition stripping reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy batteries, and in particular relates to a rechargeable fiber magnesium oxygen battery and a preparation method thereof. Background Art

[0002] Metal oxygen batteries have an open battery structure, can use oxygen as an active material to supply battery reactions, and have extremely high theoretical energy density, so they have attracted widespread attention. Among them, the magnesium negative electrode has the advantages of abundant reserves, easy storage and preparation, high theoretical capacity and low density, and magnesium oxygen batteries have high theoretical discharge voltage and energy density. Therefore, magnesium oxygen batteries are regarded as one of the potential options for the next generation of energy storage technology. According to the reversibility of the battery reaction, magnesium oxygen batteries can be divided into primary magnesium oxygen batteries and rechargeable magnesium oxygen batteries.

[0003] There have been many studies on primary magnesium oxygen batteries. However, a passivation layer is easily formed on the surface of the magnesium negative electrode, which makes it difficult for magnesium ions to pass through the passivation layer to complete the deposition of magnesium, making it difficult to realize rechargeable magnesium oxygen batteries. Compared with traditional rechargeable batteries such as lead-acid batteries and lithium-ion batteries, rechargeable magnesium oxygen batteries have the advantages of high safety, environmental friendliness, and abundant resources. They can alleviate many problems caused by insufficient lithium supply and are of great significance for large-scale storage of clean energy and reducing fossil energy consumption. Summary of the invention

[0004] In view of the problems of magnesium negative electrode surface passivation and non-rechargeable magnesium oxygen battery in the prior art, the present invention provides a rechargeable fiber magnesium oxygen battery with a magnesium negative electrode utilization rate of up to 99.8% and a discharge voltage of 1.8V and a preparation method thereof, and utilizes a zinc / magnesium-based negative electrode protective layer to achieve reversible deposition and stripping of magnesium in oxygen.

[0005] The rechargeable fiber magnesium oxygen battery based on the negative electrode protective layer provided by the present invention is a coaxial structure, and the components from the inside to the outside are: a metal magnesium wire negative electrode with a protective layer, an electrolyte layer, and a carbon nanotube film air positive electrode loaded with platinum / carbon and ruthenium dioxide. Among them, the protective layer of the metal magnesium wire is formed by the magnesium wire being treated with ZnCl2 / ethylene glycol dimethyl ether (DME) solution and H3PO4 aqueous solution in sequence; the zinc / magnesium-based surface protective layer is constructed by a simple replacement reaction, and can be firmly adhered to the surface of the magnesium negative electrode to prevent the magnesium negative electrode from reacting with air to form a passivation film; at the same time, the protective layer has the characteristics of magnesium ion conduction and electronic insulation, and can promote magnesium ions to pass through the protective layer under the drive of the electric field, ensuring the normal progress of the magnesium deposition and stripping reaction.

[0006] The preparation method of the rechargeable fiber magnesium oxygen battery based on the negative electrode protective layer provided by the present invention comprises the following specific steps:

[0007] (1) Preparation of the surface protective layer of metal magnesium wire: The negative electrode surface protective layer is constructed by a simple replacement reaction. First, at room temperature, a magnesium wire with a diameter of 0.5-0.8 mm and a length of 1-10 cm is polished and transferred to a glove box; then, the magnesium wire is treated in 0.1-1M ZnCl2 / DME for 1-24 hours, and washed with DME. After standing for 1-24 hours, the reacted magnesium wire is removed from the glove box; then, at room temperature, the magnesium wire is soaked in a 0.1-1M H3PO4 aqueous solution for 10-30 minutes, and washed with deionized water; finally, the treated magnesium wire is placed in a 60-80°C forced air oven and dried for 1-3 hours to obtain a magnesium negative electrode with a protective layer;

[0008] (2) Preparation of electrolyte: The preparation of electrolyte was carried out in a glove box filled with argon. Weigh 0.2-0.8M MgCl2, 0.2-0.8M AlCl3 and 30-60mg / mL magnesium powder (60-200 mesh) and add them to tetraethylene glycol dimethyl ether, stir at 45-60oC for 24-72h; centrifuge the solution (5000-8000rpm for 30-120min), and take the supernatant as the electrolyte;

[0009] (3) Preparation of positive electrode: Pt / C and ruthenium dioxide powders are uniformly dispersed in anhydrous ethanol, dropped onto a plurality of stacked carbon nanotube films, and dried to obtain a positive electrode;

[0010] (4) Assembly of fiber magnesium oxygen battery: The assembly of rechargeable fiber magnesium oxygen battery is carried out in a glove box filled with argon. First, the diaphragm is cut into strips of a certain size, and the glass fiber diaphragm is wetted with alcohol and wrapped on the surface of the metal magnesium wire with a protective layer; then the carbon nanotube film loaded with platinum / carbon and ruthenium dioxide is wrapped on the outside of the glass fiber diaphragm; then an appropriate amount of electrolyte is injected into the fiber battery diaphragm layer to complete the preparation of the rechargeable fiber magnesium oxygen battery.

[0011] Furthermore, the specific preparation process of the surface protective layer of the metal magnesium wire in step (1) is as follows: a magnesium wire with a diameter of 0.5 mm and a length of about 1 cm is polished with sandpaper, and is strictly sealed and transferred to a glove box; the magnesium wire is then treated in 0.1M ZnCl2 / DME for 24 hours, and then washed with DME three times, and allowed to stand for 24 hours to wait for the DME to evaporate naturally; the reacted magnesium wire is then removed from the glove box, and soaked in a 0.5M H3PO4 aqueous solution for 10 minutes, and then taken out and washed three times in deionized water, and the residual water on the surface is carefully wiped dry; finally, the treated magnesium wire is placed in a 60°C forced air oven and allowed to stand for 1 hour to completely dry the electrode to obtain a magnesium negative electrode with a protective layer.

[0012] Further, the specific preparation process of the electrolyte in step (2) is as follows: first, weigh 381 mg MgCl2, 533 mg AlCl3 and 380 mg magnesium powder (60 mesh) and add them to 10 mL tetraethylene glycol dimethyl ether, and stir at 45°C for 48 hours. Then, centrifuge the solution and take the supernatant as the electrolyte (centrifuge at 5000 rpm for 90 minutes). The preparation of the above electrolyte is carried out in a glove box filled with argon.

[0013] Furthermore, the specific preparation process of the air electrode in step (3) is as follows: First, weigh 25 mg of platinum / carbon and ruthenium dioxide respectively and disperse them in 10 mL of anhydrous ethanol. After stirring for 24 hours, ultrasonicate in an ultrasonic cleaner for 20 minutes to obtain a uniformly dispersed suspension. Then, add 60-80 μL of the above suspension onto the cut carbon nanotube film (length 0.8 cm, width 0.6-0.8 cm). Finally, stand on a hot plate at 60°C for 1 hour to allow the solvent to completely evaporate to obtain the positive electrode.

[0014] Furthermore, the specific assembly process of the fiber magnesium oxygen battery in step (4) is as follows: first, the glass fiber diaphragm is cut into 3-6 mm long strips, the glass fiber diaphragm is wetted with alcohol, and then wrapped on the surface of the metal magnesium wire with a protective layer; then, the carbon nanotube film loaded with platinum / carbon and ruthenium dioxide is wrapped on the outside of the glass fiber diaphragm; then, 20-40 μL of electrolyte is injected into the fiber battery diaphragm layer with a pipette gun to complete the preparation of the rechargeable fiber magnesium oxygen battery. The above assembly process is carried out in a glove box filled with argon.

[0015] The rechargeable fiber magnesium oxygen battery based on the negative electrode protective layer obtained by the above preparation method has a simple structure, is easy to assemble, and has rechargeability and high energy density.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] (1) The zinc / magnesium-based surface protective layer can promote the stripping of the fiber magnesium anode, so that the assembled fiber magnesium oxygen battery exhibits a magnesium anode utilization rate of up to 99.8% and a discharge voltage of 1.8V.

[0018] (2) The zinc / magnesium-based surface protective layer can firmly adhere to the surface of the magnesium negative electrode, preventing the magnesium negative electrode from reacting with air to form a passivation layer. At the same time, it has both magnesium ion conductivity and electronic insulation properties. Under the drive of the electric field, it can promote the transmembrane transmission of magnesium ions, ensure the normal progress of the magnesium deposition and stripping reaction, and ensure that the fiber magnesium oxygen battery can complete a reversible charge and discharge cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The single discharge curve of the magnesium oxygen fiber battery assembled with the magnesium negative electrode with and without the zinc / magnesium-based protective layer in the examples and comparative examples.

[0020] Figure 2 This is the charge and discharge curve of the magnesium oxygen fiber battery assembled with the magnesium negative electrode without the zinc / magnesium-based protective layer in the comparative example.

[0021] Figure 3 1 is the charge and discharge curve of the magnesium oxygen fiber battery assembled with the magnesium negative electrode having the zinc / magnesium-based protective layer in the embodiment. DETAILED DESCRIPTION

[0022] The present invention will be described in detail below with reference to the accompanying drawings and embodiments. It should be noted that, for those skilled in the art, several changes and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

[0023] The reagents used in the following examples were all purchased from outside, such as zinc chloride (98%) and anhydrous magnesium chloride (99.99%) purchased from MacLean Biochemical Technology Co., Ltd.

[0024] Aluminum chloride (99.999%) was purchased from J&K Technologies.

[0025] Phosphoric acid (AR, ≥85.0%) was purchased from Nanjing Chemical Reagent Co., Ltd.

[0026] Ethylene glycol dimethyl ether (99%) was purchased from Merrill Chemical Technology Co., Ltd.

[0027] Tetraethylene glycol dimethyl ether (99%) was purchased from Aladdin Biochemical Technology Co., Ltd.

[0028] Magnesium wire was purchased from Jingjun New Material Technology Co., Ltd.

[0029] Comparative Example 1

[0030] (1) Preparation of electrolyte: The preparation of electrolyte was carried out in a glove box filled with argon. First, 381 mg MgCl2, 533 mg AlCl3 and 380 mg magnesium powder (60 mesh) were weighed and added to 10 mL tetraethylene glycol dimethyl ether and stirred at 45°C for 48 h. Then, the solution was centrifuged and the supernatant was taken as the electrolyte (centrifugation at 5000 rpm for 90 min).

[0031] (2) Preparation of positive electrode: First, weigh 25 mg of platinum / carbon and ruthenium dioxide respectively and disperse them in 10 mL of anhydrous ethanol. After stirring for 24 hours, ultrasonicate in an ultrasonic cleaner for 20 minutes to obtain a uniformly dispersed suspension. Then, add 60-80 μL of the above suspension onto the cut carbon nanotube film (length 0.8 cm, width 0.6-0.8 cm). Finally, place it on a hot plate at 60°C for 1 hour to allow the solvent to evaporate completely to obtain the positive electrode.

[0032] (3) Assembly of fiber magnesium oxygen battery: First, cut the glass fiber diaphragm into 3-6 mm strips, wet the glass fiber diaphragm with alcohol, and wrap it on the polished surface of metal magnesium wire; then wrap the carbon nanotube film loaded with platinum / carbon and ruthenium dioxide on the outside of the glass fiber diaphragm; then use a pipette to inject 20-40 μL of electrolyte into the fiber battery diaphragm layer to complete the preparation of the rechargeable fiber magnesium oxygen battery. The above assembly process is carried out in a glove box filled with argon.

[0033] The Wuhan LAND battery performance tester was used to test the primary discharge performance of the rechargeable fiber magnesium oxygen battery. Figure 1 As shown, the magnesium oxygen battery of Comparative Example 1 experienced a continuous drop in voltage during the discharge process. This is due to the formation and gradual growth of the passivation layer on the surface of the magnesium negative electrode, which leads to a continuous increase in the polarization degree of the battery during the discharge process. At the beginning of the discharge of Comparative Example 1 (discharge specific capacity of 100 mAh g-1), the discharge voltage dropped significantly, which shows that the ion insulating film was quickly formed at the beginning, greatly reducing the reaction activity of the electrode.

[0034] The charge and discharge performance of the rechargeable fiber magnesium oxygen battery was tested using the Wuhan LAND battery performance tester, with the discharge capacity set to 250 mAh g -1 .like Figure 2 As shown, when charging, the overpotential of Comparative Example 1 increases rapidly, and the charging voltage quickly exceeds 5V, indicating that the chargeability is extremely poor.

[0035] Example 1

[0036] (1) Preparation of protective layer on the surface of magnesium wire: A magnesium wire with a diameter of 0.5 mm and a length of about 1 cm was polished with sandpaper at room temperature, and then tightly sealed and transferred to a glove box; the magnesium wire was then treated in 0.1 M ZnCl2 / DME for 24 h, and then washed with DME three times, and allowed to stand for 24 h, waiting for the DME to evaporate naturally; the reacted magnesium wire was then removed from the glove box, and soaked in a 0.5 M H3PO4 aqueous solution for 10 min at room temperature, and then washed three times in deionized water, and the residual water on the surface was carefully wiped dry; finally, the treated magnesium wire was placed in a 60°C forced air oven and allowed to stand for 1 h to completely dry the electrode, thereby obtaining a magnesium negative electrode with a protective layer.

[0037] (2) Preparation of electrolyte: First, 381 mg MgCl2, 533 mg AlCl3 and 380 mg magnesium powder (60 mesh) were weighed and added to 10 mL tetraethylene glycol dimethyl ether, and stirred at 45°C for 48 h. Then, the solution was centrifuged and the supernatant was taken as the electrolyte (centrifugation at 5000 rpm for 90 min). The preparation of the above electrolyte was carried out in a glove box filled with argon.

[0038] (3) Preparation of positive electrode: First, weigh 25 mg of platinum / carbon and ruthenium dioxide respectively and disperse them in 10 mL of anhydrous ethanol. After stirring for 24 hours, ultrasonicate in an ultrasonic cleaner for 20 minutes to obtain a uniformly dispersed suspension. Then, add 60 μL of the above suspension onto the cut carbon nanotube film (length 0.8 cm, width 0.8 cm). Finally, place it on a hot plate at 60°C for 1 hour to allow the solvent to completely evaporate to obtain the positive electrode.

[0039] (4) Assembly of fiber magnesium oxygen battery: First, cut the glass fiber diaphragm into 6 mm strips, wet the glass fiber diaphragm with alcohol, and wrap it on the surface of the metal magnesium wire with a protective layer; then wrap the carbon nanotube film loaded with platinum / carbon and ruthenium dioxide on the outside of the glass fiber diaphragm; then use a pipette to inject 20 μL of electrolyte into the fiber battery diaphragm layer to complete the preparation of the rechargeable fiber magnesium oxygen battery. The above assembly process is carried out in a glove box filled with argon.

[0040] The Wuhan LAND battery performance tester was used to test the primary discharge performance of the rechargeable fiber magnesium oxygen battery. Figure 1 As shown, the discharge voltage of the magnesium-oxygen battery based on the magnesium negative electrode of Example 1 was greatly reduced when the discharge specific capacity was 1800 mAh g-1. The battery finally showed a negative electrode utilization rate of up to 99.8%. This is because the zinc / magnesium-based surface protective layer can delay the generation of the ion insulating film on the surface of the magnesium negative electrode, thereby playing a beneficial protective role on the magnesium negative electrode.

[0041] like Figure 3 As shown, the magnesium oxygen battery based on Example 1 can smoothly realize a complete charge and discharge cycle, and the overpotential of the first charge is only 1.2V, the discharge voltage is as high as 1.80V, and has higher reaction activity.

[0042] Example 2

[0043] (1) Preparation of protective layer on the surface of magnesium wire: A magnesium wire with a diameter of 0.5 mm and a length of about 1 cm was polished with sandpaper at room temperature, and then tightly sealed and transferred to a glove box; the magnesium wire was then treated in 0.5 M ZnCl2 / DME for 24 h, then washed three times with DME, left to stand for 24 h, and allowed to evaporate naturally; the reacted magnesium wire was then removed from the glove box and soaked in a 1 M H3PO4 aqueous solution for 10 min at room temperature, then washed three times in deionized water, and the residual water on the surface was carefully wiped dry; finally, the treated magnesium wire was placed in a 60°C forced air oven and left to stand for 1 h to completely dry the electrode, thereby obtaining a magnesium negative electrode with a protective layer.

[0044] (2) Preparation of electrolyte: First, 381 mg MgCl2, 533 mg AlCl3 and 380 mg magnesium powder (60 mesh) were weighed and added to 10 mL tetraethylene glycol dimethyl ether, and stirred at 45°C for 48 h. Then, the solution was centrifuged and the supernatant was taken as the electrolyte (centrifugation at 5000 rpm for 90 min). The preparation of the above electrolyte was carried out in a glove box filled with argon.

[0045] (3) Preparation of positive electrode: First, weigh 25 mg of platinum / carbon and ruthenium dioxide respectively and disperse them in 10 mL of anhydrous ethanol. After stirring for 24 hours, ultrasonicate in an ultrasonic cleaner for 20 minutes to obtain a uniformly dispersed suspension. Then, add 60 μL of the above suspension onto the cut carbon nanotube film (length 0.8 cm, width 0.6 cm). Finally, place it on a hot plate at 60°C for 1 hour to allow the solvent to completely evaporate to obtain the positive electrode.

[0046] (4) Assembly of fiber magnesium oxygen battery: First, cut the glass fiber diaphragm into 6 mm strips, wet the glass fiber diaphragm with alcohol, and wrap it on the surface of the metal magnesium wire with a protective layer; then wrap the carbon nanotube film loaded with platinum / carbon and ruthenium dioxide on the outside of the glass fiber diaphragm; then use a pipette to inject 20 μL of electrolyte into the fiber battery diaphragm layer to complete the preparation of the rechargeable fiber magnesium oxygen battery. The above assembly process is carried out in a glove box filled with argon.

[0047] The primary discharge performance of the rechargeable fiber magnesium oxygen battery was tested using a Wuhan LAND battery performance tester. The magnesium oxygen battery based on Example 2 ultimately showed a negative electrode utilization rate of up to 98.2%. This is because the zinc / magnesium-based surface protective layer can delay the generation of an ion insulating film on the surface of the magnesium negative electrode, thereby playing a beneficial protective role on the magnesium negative electrode.

[0048] The magnesium oxygen battery based on Example 2 can smoothly realize a complete charge and discharge cycle, and the overpotential of the first charge is only 1.2V, the discharge voltage is as high as 1.75V, and has higher reaction activity.

[0049] Example 3

[0050] (1) Preparation of a protective layer on the surface of a magnesium wire: A magnesium wire with a diameter of 0.5 mm and a length of about 5 cm was polished to a bright finish with sandpaper at room temperature, and then tightly sealed and transferred to a glove box; the magnesium wire was then treated in 0.5 M ZnCl2 / DME for 24 h, and then washed three times with DME, and allowed to stand for 24 h, waiting for the DME to evaporate naturally; the reacted magnesium wire was then removed from the glove box, and soaked in a 1 M H3PO4 aqueous solution for 10 min at room temperature, and then washed three times in deionized water, and the residual water on the surface was carefully wiped dry; finally, the treated magnesium wire was placed in a 60°C forced air oven and allowed to stand for 1 h to completely dry the electrode, thereby obtaining a magnesium negative electrode with a protective layer.

[0051] (2) Preparation of electrolyte: First, 381 mg MgCl2, 533 mg AlCl3 and 380 mg magnesium powder (60 mesh) were weighed and added to 10 mL tetraethylene glycol dimethyl ether, and stirred at 45°C for 48 h. Then, the solution was centrifuged and the supernatant was taken as the electrolyte (centrifugation at 5000 rpm for 90 min). The preparation of the above electrolyte was carried out in a glove box filled with argon.

[0052] (3) Preparation of positive electrode: First, weigh 25 mg of platinum / carbon and ruthenium dioxide respectively and disperse them in 10 mL of anhydrous ethanol. After stirring for 24 hours, ultrasonicate in an ultrasonic cleaner for 20 minutes to obtain a uniformly dispersed suspension. Then, add 300 μL of the above suspension onto the cut carbon nanotube film (4 cm long and 0.6 cm wide). Finally, place it on a hot plate at 60°C for 1 hour to allow the solvent to evaporate completely to obtain the positive electrode.

[0053] (4) Assembly of fiber magnesium oxygen battery: First, cut the glass fiber diaphragm into 6 mm strips, wet the glass fiber diaphragm with alcohol, and wrap it on the surface of the metal magnesium wire with a protective layer; then wrap the carbon nanotube film loaded with platinum / carbon and ruthenium dioxide on the outside of the glass fiber diaphragm; then use a pipette to inject 100 μL of electrolyte into the fiber battery diaphragm layer to complete the preparation of the rechargeable fiber magnesium oxygen battery. The above assembly process is carried out in a glove box filled with argon.

[0054] The primary discharge performance of the rechargeable fiber magnesium oxygen battery was tested using a Wuhan LAND battery performance tester. The magnesium oxygen battery based on Example 3 finally showed a negative electrode utilization rate of up to 75.1%. This is because the zinc / magnesium-based surface protective layer can delay the generation of an ion insulating film on the surface of the magnesium negative electrode, thereby playing a beneficial protective role on the magnesium negative electrode.

[0055] The magnesium oxygen battery based on Example 3 can smoothly realize a complete charge and discharge cycle, and the overpotential of the first charge is only 1.2V, the discharge voltage is as high as 1.8V, and has higher reaction activity.

Claims

1. A rechargeable fiber magnesium oxygen battery based on a negative electrode protective layer, characterized in that: It is a coaxial structure, and the components from the inside to the outside are: a metal magnesium wire negative electrode with a protective layer, an electrolyte layer, and a carbon nanotube film air positive electrode loaded with platinum / carbon and ruthenium dioxide; wherein, the protective layer of the metal magnesium wire is formed by treating the magnesium wire with a ZnCl2 / DME solution and an H3PO4 aqueous solution in sequence, and is firmly adhered to the surface of the magnesium wire to prevent the magnesium negative electrode from reacting with the air to produce a passivation layer; the protective layer has the characteristics of magnesium ion conduction and electronic insulation, and can promote the cross-membrane transport of magnesium ions under the drive of an electric field, ensuring the normal progress of the magnesium negative electrode deposition and stripping reaction.

2. The method for preparing a rechargeable fiber magnesium oxygen battery according to claim 1, characterized in that: The specific steps are: (1) Preparation of a protective layer on the surface of a magnesium wire: First, a magnesium wire with a diameter of 0.5 to 0.8 mm and a length of 1 to 10 cm is polished and transferred to a glove box at room temperature; the magnesium wire is treated in 0.1 to 1 M ZnCl2 / DME for 1 to 24 h, and washed with DME. After standing for 1 to 24 h, the reacted magnesium wire is removed from the glove box; then, the magnesium wire is soaked in a 0.1 to 1 M H3PO4 aqueous solution for 10 to 30 min at room temperature, and washed with deionized water; finally, the treated magnesium wire is placed in a 60 to 80° C. forced air oven and dried for 1 to 3 h to obtain a magnesium negative electrode with a protective layer; (2) Preparation of electrolyte: The preparation of electrolyte was carried out in a glove box filled with argon. 0.2-0.8M MgCl2, 0.2-0.8M AlCl3 and 30-60mg / mL 60-200 mesh magnesium powder were weighed and added to tetraethylene glycol dimethyl ether, and stirred at 45-60°C for 24-72h. The solution was centrifuged at 5000-8000rpm for 30-120min, and the supernatant was taken as the electrolyte. (3) Preparation of positive electrode: Pt / C and ruthenium dioxide powders are uniformly dispersed in anhydrous ethanol, dropped onto a plurality of stacked carbon nanotube films, and dried to obtain a positive electrode; (4) Assembly of fiber magnesium oxygen battery: This is carried out in a glove box filled with argon gas. First, the diaphragm is cut into strips of a certain size, and the glass fiber diaphragm is wetted with alcohol and then wrapped on the surface of the metal magnesium wire with a protective layer. Then, a carbon nanotube film loaded with platinum / carbon and ruthenium dioxide is wrapped on the outside of the glass fiber diaphragm; then, an appropriate amount of electrolyte is injected into the fiber battery diaphragm layer to complete the preparation of the rechargeable fiber magnesium oxygen battery.

3. The preparation method according to claim 2, characterized in that: The specific preparation process of the surface protective layer of the metal magnesium wire in step (1) is as follows: use sandpaper to polish the magnesium wire with a diameter of 0.5-0.8 mm and a length of 1-10 cm to make it bright, and then seal and transfer it to a glove box; then treat the magnesium wire in 0.1M ZnCl2 / DME for 24 hours, then wash it three times with DME, and let it stand for 24 hours to wait for the DME to evaporate naturally; then move the reacted magnesium wire out of the glove box, soak it in 0.5M H3PO4 aqueous solution for 10 minutes, take it out and wash it three times in deionized water, and carefully wipe off the water remaining on the surface; finally, put the treated magnesium wire into a 60°C forced air oven and let it stand for 1 hour to completely dry the electrode to obtain a magnesium negative electrode with a protective layer.

4. The preparation method according to claim 2, characterized in that: The specific preparation process of the electrolyte in step (2) is as follows: first, weigh 381 mg MgCl2, 533 mg AlCl3 and 380 mg of 60-mesh magnesium powder, add them into 10 mL tetraethylene glycol dimethyl ether, and stir at 45°C for 48 hours; then, centrifuge the solution and take the supernatant as the electrolyte.

5. The preparation method according to claim 2, characterized in that: The specific preparation process of the air electrode in step (3) is as follows: first, weigh 25 mg of platinum / carbon and ruthenium dioxide respectively and disperse them in 10 mL of anhydrous ethanol; after stirring for 24 hours, ultrasonicate in an ultrasonic cleaner for 20 minutes to obtain a uniformly dispersed suspension; then, add 60-80 μL of the above suspension onto the cut carbon nanotube film; finally, stand on a hot plate at 60°C for 1 hour to allow the solvent to completely evaporate to obtain the positive electrode.

6. The preparation method according to claim 2, characterized in that: The specific assembly process of the fiber magnesium oxygen battery in step (4) is as follows: first, the glass fiber separator is cut into 3-6 mm long strips, the glass fiber separator is moistened with alcohol, and then wrapped on the surface of the metal magnesium wire with a protective layer; Then, a carbon nanotube film loaded with platinum / carbon and ruthenium dioxide is wrapped on the outside of the glass fiber diaphragm; then, 20-40 μL of electrolyte is injected into the fiber battery diaphragm layer using a pipette to complete the preparation of the rechargeable fiber magnesium oxygen battery.

Citation Information

Cited By

  • Water-triggered fibrous magnesium air battery, preparation method thereof and fabric battery

    CN121332041A

  • Magnesium-oxygen battery

    TWI928854B